POTENSI EKOWISATA PANTAI MOLOTABU KABUPATEN BONE BOLANGO BERDASARKAN ANALISIS SPASIAL EKOLOGIS (The Potential of Molotabu Beach Ecotourism, Bone Bolango Regency Based on Ecological Spatial Analysis) - Sunarty Suly Eraku; Mohamad Karmin Baruadi; Aang Panji Permana; Hendra Hendra; Nurdin Mohamad (Universitas Muhammadiyah Gorontalo, 2020)
Abstract - The development of the coastal area in Bone Bolango Regency is a huge potential for ecotourism. Ecotourism development focuses on aspects of nature conservation, aspects of socio-cultural and economic empowerment of local communities, aspects of learning and education. One of the ecotourism potentials of coastal areas in Bone Bolango Regency is the Molotabu beach area. The purpose of this research is to analyze the potential of the Molotabu beach ecotourism area based on the physical parameters of the socio-cultural, economic and institutional parameters. To achieve this purpose, an ecological spatial approach is used using the Geographical Information System. Field observation research methods consisted of direct measurements, interviews, and questionnaires. The research analysis used quantitatively, namely descriptive statistical analysis, scoring analysis and qualitative descriptive analysis for the final assessment of the potential of Molotabu beach ecotourism. Based on the results of the analysis of the physical parameters of the beach, namely vegetation, environmental cleanliness, beach material and water transparency, Molotabu beach has high potential. The same results were also obtained for the measurement of physical parameters including distance, infrastructure, accessibility and attractiveness of the Molotabu beach ecotourism area. High potential for ecotourism is also obtained from criteria based on institutional, socio-cultural, economic and environmental parameters. The high potential of Molotabu Beach ecotourism is because this coastal area has the potential for natural scenery, underwater beauty, crafts, regional arts and culinary.